2017
DOI: 10.4103/aer.aer_9_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of intravenous esmolol, labetalol and lignocaine in low doses for attenuation of sympathomimetic responses to laryngoscopy and endotracheal intubation

Abstract: Background:Direct layngoscopy and endotracheal intubation is a noxious stimuli and induces sympathomimetic responses. Although well tolerated in healthy subjects, it may impose life threatening arrhythmias, left ventricular failure or rupture of cerebral aneurysm in susceptible patients. Esmolol, Labetalol and Lignocaine attenuate these responses but are associated with side effects of bradycardia, hypotension etc. In lower doses, chances of these side effects are comparatively low. So we designed this prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the study conducted by Younes M M et al 13 comparing labetalol with fentanyl and lidocaine, Labetalol was better in attenuation of haemodynamic stress response to extubation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the study conducted by Younes M M et al 13 comparing labetalol with fentanyl and lidocaine, Labetalol was better in attenuation of haemodynamic stress response to extubation.…”
Section: Discussionmentioning
confidence: 96%
“…In the studies conducted by Ratnani et al, 13 Jaiswal A et al, 14 Anand KJ et al 15 Labetalol effectively suppressed the sympathoadrenal response to intubation.…”
Section: Discussionmentioning
confidence: 97%
“…28 It is commonly used to reverse hypertension or induce hypotension in the operative and perioperative settings. [29][30][31][32] In these settings, esmolol has accrued a favorable safety profile, largely owing to its rapid titratability. As prior studies have shown, 33 we found that esmolol significantly decreased contractility and cardiac output in our model, with a relative sparing of diastolic function.…”
Section: Hemodynamic Effects Of Esmololmentioning
confidence: 99%
“…Cough during emergence from general anesthesia increases blood pressure, heart rate (HR) and myocardial ischemia, bronchospasm, and bleeding, 8 multiplies the pain caused by surgery, and increases intracranial and intraocular pressure in patients with brain involvement or glaucoma. 9 10 Range of methods is available, such as local and intravenous injection of topical anesthetics to reduce cough.…”
Section: Introductionmentioning
confidence: 99%